Outcome and Complications Following Medial Patellar Luxation Corrective Surgery with Tibial Tuberosity Transposition Using a Locking Plate and a Pin Fixation: 45 Unilateral and 20 Single-Session Bilateral Procedures - Eskelinen, Esa V.; Suhonen, Ari P.; Virolainen, Juha V.; Liska, William D. (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objectives To evaluate the outcome and complications in dogs with medial patellar luxation (MPL) undergoing tibial tuberosity transposition (TTT) with a locking plate and pin fixation (Plate–Pin).Methods This retrospective multicenter study included 65 consecutive MPL stifle surgeries using tibial tuberosity (TT) fixation with a 5-hole locking plate and a pin. The median weight of the dogs was 6.2 kg. The grade of luxation was 2/4 in 50 stifles and 3/4 in 15 stifles. Outcomes were assessed during follow-up examinations 33 to 648 days after surgery with clinical examination and radiography. Canine Orthopedic Index questionnaires were sent to owners 6 to 39 months after surgery.Results Complications were reported in 14/65 stifles, of which 8/14 were minor and 6/14 were major. After treatment of the major complications, lameness was resolved in all cases and the MPL was resolved in 64/65 stifles.Clinical Significance When the surgery was performed as described in this article, Plate–Pin fixation for TT during MPL surgery is a feasible technique with a lower incidence of luxation recurrence, TT avulsion, and fractures compared with recent retrospective studies with pin and tension band wire TT fixation. Further development of the locking plate TT fixation is indicated to resolve pin-related complications and to determine if fixation including a pin is necessary.
Keywords: medial patellar luxation; tibial tuberosity transposition; locking plate fixation; unilateral surgery; single-session bilateral surgery